Wind Turbine Production Planning in Logistic Systems - Nanda Ruswandi; Dhian Febriyani Hutasuhut; May Putri Fadillah; Yizri Ievana Febrianty Rumalutur; Iwan Sukarno; Rahmad Inca Liperda (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Production planning is very important in an industrial company as well as planning in Logistics. The purpose of implementing production planning in a company is to minimize costs incurred and maximize profits. This research is practicum-based research in the laboratory with the object of observation in the form of a wind turbine toy. This object will be processed through 5 stages in the production process starting from forecasting, RCCP (Rough Cut Capacity Planning), MRP (Material Requirement Planning), CRP (Capacity Requirement Planning), and Line Balancing. forecasting results are carried out with 12 future periods producing 232,888 units, RCCP balance between available capacity and required capacity, MRP using the lot sizing technique obtains the cheapest cost per unit Rp.142,179 with the LTC (Least Total Cost) method when compared to other MRP methods, namely LFL (Lot for Lot), POQ (Period Order Quantity), PPB (Part Period Balancing), EOQ (Economic Order Quantity), and LUC (Least Unit Cost), CRP by calculating the number of machines and working time, and line balancing which results in a decrease in track ineffectiveness from 42% to 22% and Smoothness Index from 476,662 to 189,703.